Photovoltaic power control algorithms using bess - Kim, Jun Sung; Na, Ui Kyun; Song, Jae Ju; Jung, Jae Sung (Transactions of the Korean Institute of Electrical Engineers, 2021)
In the case of renewable energy, power generation is affected by factors such as the external climate environment. In order to efficiently storage and use of renewable energy, Battery Energy Storage Systems (BESS) are being used. However, BESS faced issues such as fire accident and stability due to lack of optimization operating system. In this paper, we propose a predict system of solar power generation using the ANN(Artificial Neural Network) and an BESS operation scheduling algorithm for BESS optimization. In this paper, we verified the proposed algorithm for real-time output compensation service and BESS operation stability, and we expect to address the safety issues of BESS.
Keywords: ANN (artificial neural network); Battery energy storage systems; Fire accident; Operation scheduling; Operation stability; Photovoltaic power; Renewable energies; Use of renewable energies; Artificial Neural Network; Battery Energy Storage System; Operation Scheduling; Photovoltaic